STUDI LITERATUR: EFEKTIVITAS PENGGUNAAN POC URIN KELINCI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS - Ahmad Aliwinarjo; Kartina AM; Susiyanti Susiyanti (Innofarm : Jurnal Inovasi Petanian, 2026)
This study aims to examine the effectiveness of Rabbit Urine Liquid Organic Fertilizer (LOF) on the growth and yield of sweet corn (Zea mays L. var. saccharata Sturt) Sweet corn is a high-value horticultural commodity with considerable yield potential; however, its field productivity is often constrained by improper use of inorganic fertilizers in terms of dosage and application frequency. Long-term dependence on synthetic chemical fertilizers may also reduce soil quality and environmental sustainability. The research employed a literature review method using secondary data obtained from SINTA-indexed journals, Google Scholar, and ResearchGate within the 2015–2024 period. The findings indicate that rabbit urine LOF contains relatively high levels of essential macronutrients, namely nitrogen (2.72%), phosphorus (1.1%), and potassium (0.5%), which are higher compared to other livestock urine. Application of rabbit urine LOF significantly improved vegetative parameters such as plant height and number of leaves, as well as generative parameters including cob length and cob weight. A dosage of 300 mL per plant or a concentration of 60 mL per liter of water showed the best results in several studies. Therefore, rabbit urine LOF has strong potential as an environmentally friendly and sustainable alternative fertilizer